Implementation of Digital Marketing Literacy in Entrepreneurship Learning to Improve Online Business Readiness - Jazuli Jazuli; Ana Dwi Setyo Lestari; Sudarmiatin Sudarmiatin; Rizky Firmansyah (International Journal of Economics and Management Research, 2024)
In today's digital age, online business has become a global phenomenon that plays an integral role in the world economy. However, at the local level, especially in Bojonegoro, there is a problem of low involvement of vocational students in online business. This is a serious concern considering that SMK should be an educational institution that is able to produce graduates who are ready to enter the world of work, including in the realm of online business. The importance of increasing digital marketing literacy in entrepreneurship learning at SMK is very important so that students can develop the skills needed to understand, manage, and optimize online businesses. Learning strategies that are integrated with digital marketing literacy are expected to provide students with a better understanding of online business concepts, digital marketing, and effective strategies in the global and local scope. This research novelty will contribute by filling these knowledge gaps and providing new insights into the development of an entrepreneurial curriculum oriented towards digital marketing literacy at the vocational level. The inability of SMK students to understand and apply digital marketing literacy can be a serious obstacle in creating a generation that is strong and ready to do business online. Therefore, this research has an urgency to improve the quality of entrepreneurship education in vocational schools. This study used a descriptive qualitative approach. The subject of the study involves Students. Data was collected through observation, interviews, and documentation. Data analysis involves the reduction, display, and inference of data, with tringulation used to ensure validity. The results of research, observations, and interviews show that learning digital marketing literacy in entrepreneurship at SMKN Ngraho Bojonegoro and SMKN Temayang Bojonegoro has contributed positively to students' understanding of online business. Involvement Students in the project- a practical and integrated learning approach have help them develop the skills and knowledge needed to succeed in a digital business environment. Although there are some areas that require additional attention, overall, this learning program can be considered successful in improving the digital marketing literacy of vocational students in both schools.